Carers' attributions about positive events in psychosis relate to expressed emotion. - Grice, S; Kuipers, E; Bebbington, P; Dunn, G; Fowler, D; Freeman, D; Garety, P (2009)
BACKGROUND: Relapse is increased in people with psychosis who live with carers with high expressed emotion (EE). Attributional style has been used to understand EE at a psychological level. Previous studies have investigated carer appraisals for negative events in the patient's life. We therefore aimed to examine spontaneous carer attributions for both negative and positive events. Further, we distinguished between high EE based on critical comments, and that based on emotional-overinvolvement. METHOD: Audiotapes of the Camberwell Family Interview (CFI) (N = 70) were rated using the Leeds Attributional Coding System (LACS). Raters were blind to previous ratings of EE. RESULTS: In our sample, low EE carers made significantly more attributions about positive events, and less about negative events than high EE carers. This is because criticism, but not overinvolvement, was strongly associated with responsibility attributions for negative events, while overinvolvement, but not criticism, was inversely associated with responsibility attributions for positive events. CONCLUSION: Carers' attributions for both positive and negative events may be a useful target for improving family interventions in psychosis.